Fast Potassium Storage in Hierarchical Ca0.5Ti2(PO4)3@C Microspheres Enabling High‐Performance Potassium‐Ion Capacitors. (15th July 2018) - Zhang, Zhongyu; Li, Malin; Gao, Yu; Wei, Zhixuan; Zhang, Meina; Wang, Chunzhong; Zeng, Yi; Zou, Bo; Chen, Gang; Du, Fei
Abstract: Hybrid potassium‐ion capacitors (KICs) show great promise for large‐scale storage on the power grid because of cost advantages, the weaker Lewis acidity of K + and low redox potential of K + /K. However, a huge challenge remains for designing high‐performance K + storage materials since K + ions are heavier and larger than Li + and Na + . Herein, the synthesis of hierarchical Ca0.5 Ti2 (PO4 )3 @C microspheres by use of the electrospraying method is reported. Benefiting from the rich vacancies in the crystal structure and rational nanostructural design, the hybrid Ca0.5 Ti2 (PO4 )3 @C electrode delivers a high reversible capacity (239 mA h g −1 ) and superior rate performance (63 mA h g −1 at 5 A g −1 ). Moreover, the KIC employing a Ca0.5 Ti2 (PO4 )3 @C anode and activated carbon cathode, affords a high energy/power density (80 W h kg −1 and 5144 W kg −1 ) in a potential window of 1.0–4.0 V, as well as a long lifespan of over 4000 cycles. In addition, in situ X‐ray diffraction is used to unravel the structural transition in Ca0.5 Ti2 (PO4 )3, suggesting a two‐phase transition above 0.5 V during the initial discharge and solid solution processes during the subsequent K + insertion/extraction. The present study demonstrates a low‐cost potassium‐based energy storage device with high energy/power densities and a long lifespan. Abstract : A hybrid potassium‐ion capacitor using hierarchical Ca0.5 Ti2 (PO4 )3 @C microspheres as anode and activated carbon as cathode is shown. The potassium‐ion storage device delivers a high power density of 5144 W kg −1 at an energy density of 34 W h Kg −1 with a long lifespan of 4000 cycles in the potential range of 1.0–4.0 V.